Controllable Aligned Nanofiber Hybrid Yarns with Enhanced Bioproperties for Tissue Engineering. Issue 7 (16th April 2019) - Liu, Chengkun; Li, Boyu; Mao, Xue; Zhang, Qing; Sun, Runjun; Gong, R. Hugh; Zhou, Fenglei
Abstract: Electrospun nanofibers have large surface area, high porosity, and controllable orientation while conventional microfibers have appropriate mechanical properties such as stiffness, strength, and elasticity. Therefore, the combination of nanofibers and microfibers can provide building elements to engineer biomimetic scaffolds for tissue engineering. In this study, a core–shell structured fibrous structure with controllable surface topography is created by electrospinning polycaprolactone (PCL) nanofibers onto polyglycolic acid (PGA) microfibers. The surface morphology, surface wettability, and mechanical properties of the resultant core–shell structure are characterized. FE‐SEM images reveal that the orientation of PCL nanofibers on the yarn surface can be tuned by a fiber collector and rotating disks. Benefiting from the introduction of a shell of aligned PCL nanofibers on the core of PGA yarn, the uniaxially aligned PCL nanofiber–covered yarns (A‐PCLs) exhibit higher hydrophilicity, porosity, and mechanical properties than the core PGA yarns. Moreover, A‐PCLs promote the adhesion and proliferation of BALB/3T3 (mouse embryonic fibroblast cell line), and guide cell growth along the biotopographic cues of the PCL nanofibers with controllable alignment. The developed core–shell yarn having both the desired surface topography of PCL nanofibers and mechanical properties of PGA microfibers demonstrates great potential in constructing various tissue scaffolds. Abstract : Controllable aligned nanofiber covered yarns are developed for tissue engineering scaffolds by a novel electrospinning process. The prepared scaffolds possess well‐aligned nanofibers with a high mechanical property, hydrophilicity, biocompatibility, and cells are able to identify the biotopographic cues provided by surface‐aligned nanofibers. These novel yarns have potential applications for constructing different tissue bioengineered structures.